‫دور‬‫القيادة‬ ‫التحويلية‬ ‫في‬ ‫تنمية‬ ‫روح‬ ‫فريق‬ ‫العمل‬ - ‬‫محمد‫ سمار ‬; ‬‫أحمد‫ ب‬‫وغاني ‬ (My University, 2018)
This study aims to highlight the role of transformational leadership of four dimensions: the influence and ideal guidance of the intellectual individual and notional and a source of motivation through the influence on the development of team spirit, and to achieve this objective, the field study was conducted in the national unit of the Ahras fat market, and relied on the form provided for this effect, where it was distributed to a study sample, which included a sample of workers and 30 workers, and relied on the spss program in data analysis and offloading, testing hypotheses and access to results. OUR study watch that THE leadership transformational affected THE development of team spirit at a low rate, and this relationship is a weak response. .